Sound, Routine (Meaning…): A Report - Dantas, Paulo; In the Field 2 CRISAP (2024)
In this presentation I will reflect on experiences that prompted me to reassess some aspects of my field recording activities. Those experiences are related to the recording sessions for Cidade Arquipélago (2015), an album predominantly featuring binaural field recordings produced in Japan, conducted between 2014-15. My subsequent 2023 research in Tokyo was motivated by the realisation that many of the album's recordings presented sonic situations commonly explored by other sound artists, potentially contributing to a stereotypical portrayal of ‘Japanese (sonic) culture’. Dissatisfied, I resolved to revisit the original recording sites, focusing not on a perceived ‘Japanesenes’ of events, but on personal memories associated with the 2014-15 recordings. The 2023 recording sessions were marked by disappointment, overshadowed by the memory of the original recordings. Consequently, I shifted focus towards exploring presence, routines, and the repetitive nature of everyday life. This led my research to gradually delve into 'sound routines' found in Tokyo, providing a means to immerse in the city's rhythms through auditory experiences. A handful of sound works emerged, documenting routine phenomena by overlaying multiple recordings of the same recurring situations, while moving away from a singular focus on 'culturally symbolic' sounds. Additionally, certain sound events served as scores for electronic instruments developed during the creative process.
FRIS
1
Keywords: Music, Thought and Technology